2012
DOI: 10.1038/ejcn.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of zinc supplementation on head circumference of Nepalese infants and toddlers: a randomized controlled trial

Abstract: BACKGROUND/OBJECTIVE: To assess the effects of micronutrient supplementation on head circumference of rural Nepali infants and children. SUBJECTS/METHODS: We used a randomized controlled trial to assess the effects of micronutrient supplementation on head circumference in 569 rural Nepali infants and children aged 4-17 months. Children were randomized to: (1) zinc, (2) iron-folic acid, (3) zinc plus iron-folic acid or (4) a placebo group. Data on head circumference were collected during five visits at B3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Zinc has been reported to have functional properties such as antioxidant, anti-inflammatory and antiapoptotic effects with its immunoregulator effects on animals and humans (Costa et al, 2012), Especially, the prenatal zinc supplementation confers a beneficial effect on the infants' neurobehavioural development and immune functions, or the rate of head growth in infants (Surkan et al, 2012). However there is concern that nano-sized materials exhibit unknown biological or environmental effects, even if their bulk counterparts are known to be safe (Yoshida et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc has been reported to have functional properties such as antioxidant, anti-inflammatory and antiapoptotic effects with its immunoregulator effects on animals and humans (Costa et al, 2012), Especially, the prenatal zinc supplementation confers a beneficial effect on the infants' neurobehavioural development and immune functions, or the rate of head growth in infants (Surkan et al, 2012). However there is concern that nano-sized materials exhibit unknown biological or environmental effects, even if their bulk counterparts are known to be safe (Yoshida et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a RCT conducted by Tielsch et al, 2007 in central Nepal, mean(SD) values of Zn were 11.0 (2.1) μmol/L in placebo and 11.8 (2.4) μmol/L in Zn supplemented children respectively [1]. Supplementation trials of Zn in pneumonia [5,6], and other diseases affecting mortality [1], anthropometry [7,8] and socio-demographic variables [9,10] have been conducted in Nepalese populations in the past decade. Prevalence and the burden of Zn deficiency in the eastern part of Nepal are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Also comes in agreement with Sur et al [22] who found in their study significant effect of zinc supplementation on weight, length and linear growth velocity at the end of 1 year only . Also Surkan PJ, et al [23] who considered as a fact that preventive zinc supplementation in populations at risk of zinc deficiency increases linear growth and weight gain among infants and young children and Hoque et al [24] in a study of 200 LBW infants also found significant effect of Zn supplementation on weight gain. However, authors did not study the effect of Zn on other growth parameters.…”
Section: Results:-mentioning
confidence: 99%